Bilateral Carotid Body Tumor: A Case Report - Kaytez, Selda Kargin; Ünlü, İlhan; Göçmen, Hakan; Samim, Erdal; Uzunkulaoğlu, Hakkı; Şahin, Ender (Fırat University, 2012)
Carotid body tumors are relatively rare paragangliomas that develop from neural crest cells at the bifurcation of the common carotid artery. Carotid body tumors are seen frequently in a sporadic form, although approximately 10% of the patients have a familial history of this disease. In the sporadic form, less than 5% of the patients have bilateral tumors. Excision is currently considered the treatment of choice. A case of non-familial bilateral carotid body tumor in a 53 year old man, who presented with 1,5 years history of tenderness and palpable neck masses bilaterally is presented.

Karotid cisim tümörleri, karotis bifurkasyonundaki nöroektodermal hücrelerden gelişen, nadir görülen tümörlerdendir. Karotid cisim tümörleri sıklıkla sporadik formda izlenirler; ancak hastaların yaklaşık %10'unda aile hikayesi vardır. Sporadik formda, hastaların %5'inden daha azında bu tümörler bilateral olarak gözlenir. Eksizyon sıklıkla tercih edilen tedavi seçeneğidir. Bu yazıda, 53 yaşında, ailesel olmayan, 1,5 yıldır ağrısız iki taraflı boyun şişliği şikayeti olan bilateral karotid cisim tümörlü erişkin bir erkek olgu tartışılmıştır.
Bilateral Karotid Cisim Tümörü: Olgu Sunumu